Amelioration of Isoproterenol-Induced Oxidative Damage in Rat Myocardium by Withania somnifera Leaf Extract - Khalil, Md. Ibrahim; Ahmmed, Istiyak; Ahmed, Romana; E. M., Tanvir; Afroz, Rizwana; Paul, Sudip; Siew, Hua Gan; Alam, Nadia (Hindawi Publishing Corporation, 2015)
We investigated the protective role of Withania somnifera leaf extract (WSLEt) on isoproterenol- (ISO-) induced myocardial infarction (MI) in rats. Subcutaneous injection of ISO (85mg/kg body weight (b.w.)) administered to rats for two consecutive days caused a significant increase in cardiac troponin I (cTnI) levels and serum lipid profiles, as well as the activities of some marker enzymes. In addition to these diagnosticmarkers, there were increased levels of lipid peroxidation (LPO) and decreased activities of enzymatic antioxidants (superoxide dismutase (SOD), glutathione peroxidase (GPx), glutathione reductase (GRx), and glutathione- S-transferase (GST)) in themyocardium.However, oral pretreatment (100mg/kg b.w.) withWSLEt for 4 weeks elicited a significant cardioprotective activity by lowering the levels of cTnI, lipid profiles, and marker enzymes. The levels of LPO products were also significantly decreased. Elevated activities of antioxidant enzymes were also observed in rats pretreated with WSLEt. As further confirmed histopathologically, our findings strongly suggest that the cardioprotective effect ofWSLEt onmyocardium experiencing ISO-induced oxidative damage may be due to an augmentation of the endogenous antioxidant system and an inhibition of LPO in the myocardial membrane.We conclude thatWSLEt confers some protection against oxidative damage in ISO-inducedMI in rats.